2021
DOI: 10.1002/vms3.617
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of cowpea (Vigna unguiculata) hay as a replacement for noug seed (Guizotia abissynica) cake in the ration of Gumuz lambs in Ethiopia

Abstract: Background:The objective of this study was to evaluate the replacement value of cowpea (Vigna unguiculata) hay for noug seed (Guizotia abissynica) cake on dry matter (DM) and nutrient intake, nutrient digestibility, body weight change, carcass characteristics and economic feasibility of the feeding regime of Gumuz lambs. Methods:The study was conducted using 25 yearling intact male lambs with an initial body weight of 18.26 ± 0.63 kg (mean ± SD).The lambs were assigned into five treatments: (T1) 272.3 g noug s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
1
1
Order By: Relevance
“…This variation may have resulted from the different basal feed used in those studies, which in this case was fodder oats. The DM, OM, ADF and NDF digestible intake reported by Shitaneh et al (2021) for Gumuz sheep supplemented with cowpea hay as a replacement for Noug seed cake was lower than the result found in the present study. However, the author reported a higher CP digestible intake value than the current study.…”
Section: Resultscontrasting
confidence: 96%
See 2 more Smart Citations
“…This variation may have resulted from the different basal feed used in those studies, which in this case was fodder oats. The DM, OM, ADF and NDF digestible intake reported by Shitaneh et al (2021) for Gumuz sheep supplemented with cowpea hay as a replacement for Noug seed cake was lower than the result found in the present study. However, the author reported a higher CP digestible intake value than the current study.…”
Section: Resultscontrasting
confidence: 96%
“…This variation in final body weight and daily gain might be attributed to the difference in the breed used, and the type and nutrient content of the dietary supplements, as well as basal feed used for the respective studies. The feed conversion efficiency in the present study was also consistent with earlier studies reported for different indigenous sheep breeds, such as Arsi-Bale ( Wegi et al, 2018 ; 0.06–0.09), Abergele ( Gebru et al, 2017 ; 0.066–0.073) and Gumuz ( Shitaneh et al, 2021 ; 0.058–0.086) breeds.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation